Triglyceride–Glucose Index as a Predictor of No-Reflow Phenomenon After Primary Percutaneous Coronary Intervention in ST-Elevation Myocardial Infarction: Systematic Review and Meta-Analysis - Mira Novia Iskandar; Schasett Augustiasmi Sumantri; Fatchurochman (International Medical Journal Corp. Ltd, 2026)
Introduction: No-reflow phenomenon remains an important complication after percutaneous coronary intervention in ST-segment elevation myocardial infarction, reflecting impaired myocardial reperfusion despite successful epicardial vessel opening. The triglyceride–glucose index is a simple surrogate marker of insulin resistance and metabolic dysfunction, but its overall association with no-reflow after PCI remains incompletely established. Objective: This systematic review and meta-analysis aimed to evaluate the predictive value of the triglyceride–glucose index for no-reflow or impaired microcirculatory reperfusion after PCI in patients with STEMI. Methods: A systematic literature search was performed in PubMed, Cochrane Library, and ScienceDirect using terms related to triglyceride–glucose index, myocardial infarction, acute coronary syndrome, and percutaneous coronary intervention. Eligible studies included patients with STEMI or closely related AMI populations undergoing PCI, evaluated TyG index as a predictor, and reported no-reflow or impaired microcirculatory reperfusion outcomes. Odds ratios and 95% confidence intervals were pooled using a random-effects model. Results: Five studies involving 2,007 patients were included. All studies were retrospective cohorts. Higher TyG index was consistently associated with increased risk of no-reflow or impaired microcirculatory reperfusion. The pooled analysis showed that elevated TyG index significantly increased the odds of no-reflow after PCI (OR 3.10, 95% CI 1.97–4.88; p<0.00001). Substantial heterogeneity was observed across studies (I²=85%), likely due to differences in population characteristics, no-reflow definitions, TyG cut-off values, and adjustment models. Discussion: The association between TyG index and no-reflow is biologically plausible because insulin resistance, hyperglycemia, and hypertriglyceridemia may promote endothelial dysfunction, oxidative stress, inflammation, platelet activation, and microvascular obstruction. These mechanisms overlap with the pathophysiology of no-reflow after PCI. The TyG index may therefore represent a practical and low-cost marker for identifying patients at increased risk of reperfusion failure. Conclusion: Higher TyG index is significantly associated with increased odds of no-reflow or impaired microcirculatory reperfusion after PCI in patients with STEMI. The TyG index may be useful for early risk stratification, although prospective validation is required before routine clinical implementation.